Probing of local polarity in poly(methyl methacrylate) with the charge transfer transition in Nile red - Yadigarli, Aydan; Song, Qimeng; Druzhinin, Sergey I.; Schönherr, Holger (Beilstein Journal of Organic Chemistry, 2019)
The permittivity of polymers and its spatial distribution play a crucial role in the behavior of thin films, such as those used, e.g., as sensor coatings. In an attempt to develop a conclusive approach to determine these quantities, the polarity of the model polymer poly(methyl methacrylate) (PMMA) in 600 nm thin films on a glass support was probed by the energy of the charge transfer transition in the oxazine dye Nile red (NR) at 25 °C. The absorption and fluorescence spectra of NR were observed to shift to the red with increasing solvent polarity, because of the intramolecular charge transfer character of the optical transition. New types of solvatochromic plots of emission frequency against absorption frequency and vice versa afforded the Onsager radius-free estimation of the ground and excited states dipole moment ratio. With this approach the values of these dipole moments of 11.97 D and 18.30–19.16 D, respectively, were obtained for NR. An effective local dielectric constant of 5.9–8.3 for PMMA thin films was calculated from the solvatochromic plot and the fluorescence maximum of NR observed in the PMMA films. The fluorescence band of NR in the rigid PMMA films shifted to the red by 130 cm−1 with increasing excitation wavelength from 470 to 540 nm, while in a series of liquids the position of the emission maximum of NR remained constant within same range of the excitation wavelength. It is concluded that the fluorescence spectrum of NR in PMMA undergoes inhomogeneous broadening due to different surroundings of NR molecules in the ground state and slow sub-glass transition (Tg) relaxations in PMMA.
Keywords: charge transfer; dipole moment; fluorescence; inhomogeneous broadening; oxazine dye; polarity probe; polymer permittivity

(untitled) - Handschuh-Wang, S.; Wesner, D.; Wang, T.; Lu, P.; Tücking, K.-S.; Haas, S.; Druzhinin, S. I.; Jiang, X.; Schönherr, H. (Macromol. Chem. Phys., 2017)

(untitled) - Sadat Ebrahimi, M. M.; Schönherr, H. (Langmuir, 2014)

(untitled) - Sadat Ebrahimi, M.-M.; Voss, Y.; Schönherr, H. (ACS Appl. Mater. Interfaces, 2015)

(untitled) - Zhou, J.; Yao, D.; Qian, Z.; Hou, S.; Li, L.; Jenkins, A. T. A.; Fan, Y. (Biomaterials, 2018)

(untitled) - Milo, S.; Thet, N. T.; Liu, D.; Nzakizwanayo, J.; Jones, B. V.; Jenkins, A. T. A. (Biosens. Bioelectron., 2016)

(untitled) - Kumar, A.; Montemagno, C.; Choi, H.-J. (Sci. Rep., 2017)

(untitled) - Mura, S.; Nicolas, J.; Couvreur, P. (Nat. Mater., 2013)

(untitled) - Karimi, M.; Ghasemi, A.; Sahandi Zangabad, P.; Rahighi, R.; Moosavi Basri, S. M.; Mirshekari, H.; Amiri, M.; Shafaei Pishabad, Z.; Aslani, A.; Bozorgomid, M.; Ghosh, D.; Beyzavi, A.; et al. (Chem. Soc. Rev., 2016)

(untitled) - Alvarez-Lorenzo, C.; Bromberg, L.; Concheiro, A. (Photochem. Photobiol., 2009)

(untitled) - Müller, S.; Cavallaro, A.; Vasilev, K.; Voelcker, N. H.; Schönherr, H. (Macromol. Chem. Phys., 2016)

(untitled) - Voß, Y.; Wassel, E.; Jiang, S.; Song, Q.; Druzhinin, S. I.; Schönherr, H. (Macromol. Biosci., 2017)

(untitled) - Tücking, K.-S.; Handschuh-Wang, S.; Schönherr, H. (Aust. J. Chem., 2014)

(untitled) - Frank, B.; Gast, A. P.; Russell, T. P.; Brown, H. R.; Hawker, C. (Macromolecules, 1996)

(untitled) - Haas, S.; Hain, N.; Raoufi, M.; Handschuh-Wang, S.; Wang, T.; Jiang, X.; Schönherr, H. (Biomacromolecules, 2015)

(untitled) - Hess, C. M.; Riley, E. A.; Palos-Chávez, J.; Reid, P. J. (J. Phys. Chem. B, 2013)

(untitled) - Greenspan, P.; Mayer, E. P.; Fowler, S. D. (J. Cell Biol., 1985)

(untitled) - Sackett, D. L.; Wolff, J. (Anal. Biochem., 1987)

(untitled) - Kucherak, O. A.; Oncul, S.; Darwich, Z.; Yushchenko, D. A.; Arntz, Y.; Didier, P.; Mély, Y.; Klymchenko, A. S. (J. Am. Chem. Soc., 2010)

(untitled) - Levitt, J. A.; Chung, P.-H.; Suhling, K. (J. Biomed. Opt., 2015)

(untitled) - Synak, A.; Bojarski, P.; Grobelna, B.; Gryczyński, I.; Fudala, R.; Mońka, M. (Opt. Mater., 2018)

(untitled) - Jee, A.-Y.; Park, S.; Kwon, H.; Lee, M. (Chem. Phys. Lett., 2009)

(untitled) - Zhang, Y.; Zhang, Z.; Ding, Y.; Pikramenou, Z.; Li, Y. (ACS Appl. Mater. Interfaces, 2019)

(untitled) - Chiang, C.-L.; Wu, M.-F.; Dai, D.-C.; Wen, Y.-S.; Wang, J.-K.; Chen, C.-T. (Adv. Funct. Mater., 2005)

(untitled) - Camargo Dias, L., Jr; Custodio, R.; Pessine, F. B. T. (Chem. Phys. Lett., 1999)

(untitled) - Yablon, D. G.; Schilowitz, A. M. (Appl. Spectrosc., 2004)

(untitled) - Zuehlsdorff, T. J.; Haynes, P. D.; Payne, M. C.; Hine, N. D. M. (J. Chem. Phys., 2017)

(untitled) - Crider, P. S.; Majewski, M. R.; Zhang, J.; Oukris, H.; Israeloff, N. E. (Appl. Phys. Lett., 2007)

(untitled) - Ardi, M. S.; Dick, W.; Kubát, J. (Colloid Polym. Sci., 1993)

(untitled) - Bergman, R.; Alvarez, F.; Alegría, A.; Colmenero, J. (J. Chem. Phys., 1998)

(untitled) - Sane, S. B.; Knauss, W. G. (Mech. Time-Depend. Mater., 2001)

(untitled) - Sane, S. B.; Knauss, W. G. (Mech. Time-Depend. Mater., 2001)

(untitled) - de Deus, J. F.; Souza, G. P.; Corradini, W. A.; Atvars, T. D. Z.; Akcelrud, L. (Macromolecules, 2004)

(untitled) - Schmidt-Rohr, K.; Kulik, A. S.; Beckham, H. W.; Ohlemacher, A.; Pawelzik, U.; Boeffel, C.; Spiess, H. W. (Macromolecules, 1994)

Anelastic and Dielectric Effects in Polymeric Solids - McCrum, N. G.; Read, B. E.; Williams, G. (John Wiley & Sons, 1967)

(untitled) - Moog, R. S.; Kim, D. D.; Oberle, J. J.; Ostrowski, S. G. (J. Phys. Chem. A, 2004)

(untitled) - Ernsting, N. P.; Breffke, J.; Vorobyev, D. Y.; Duncan, D. A.; Pfeffer, I. (Phys. Chem. Chem. Phys., 2008)

(untitled) - Druzhinin, S. I.; Galievsky, V. A.; Yoshihara, T.; Zachariasse, K. A. (J. Phys. Chem. A, 2006)

(untitled) - Zachariasse, K. A.; Druzhinin, S. I.; Bosch, W.; Machinek, R. (J. Am. Chem. Soc., 2004)

(untitled) - Galievsky, V. A.; Druzhinin, S. I.; Demeter, A.; Jiang, Y.-B.; Kovalenko, S. A.; Pérez Lustres, L.; Venugopal, K.; Ernsting, N. P.; Allonas, X.; Noltemeyer, M.; Machinek, R.; Zachariasse, K. A. (ChemPhysChem, 2005)

(untitled) - Zhang, X.-X.; Liang, M.; Ernsting, N. P.; Maroncelli, M. (J. Phys. Chem. B, 2013)

(untitled) - Andreatta, D.; Sen, S.; Pérez Lustres, J. L.; Kovalenko, S. A.; Ernsting, N. P.; Murphy, C. J.; Coleman, R. S.; Berg, M. A. (J. Am. Chem. Soc., 2006)

(untitled) - Baumann, W.; Bischof, H.; Fröhling, J.-C.; Brittinger, C.; Rettig, W.; Rotkiewicz, K. (J. Photochem. Photobiol., A, 1992)

(untitled) - Lippert, E. (Z. Naturforsch., A: Astrophys., Phys. Phys. Chem., 1955)

(untitled) - Golini, C. M.; Williams, B. W.; Foresman, J. B. (J. Fluoresc., 1998)

(untitled) - Klymchenko, A. S.; Duportail, G.; Demchenko, A. P.; Mély, Y. (Biophys. J., 2004)

(untitled) - Ghoneim, N.; Suppan, P. (J. Lumin., 1989)

(untitled) - Ghoneim, N. (Spectrochim. Acta, Part A, 2000)

(untitled) - Renge, I. (J. Photochem. Photobiol., A, 2018)

Landolt-Börnstein. Numerical Data and Functional Relationships in Science and Technology - Group IV Physical Chemistry - Madelung, O. (Static Dielectric Constants of Pure Liquids and Binary Liquid Mixtures, 1991)

Landolt-Börnstein. Numerical Data and Functional Relationships in Science and Technology - Group III Condensed Matter - Lechner, M. D. (Optical Constants. Refractive Indices of Organic Liquids, 1996)

(untitled) - Dutt, G. B.; Doraiswamy, S.; Periasamy, N.; Venkataraman, B. (J. Chem. Phys., 1990)

(untitled) - Dutt, G. B.; Doraiswamy, S.; Periasamy, N. (J. Chem. Phys., 1991)

(untitled) - Reiser, D.; Laubereau, A. (Ber. Bunsen-Ges., 1982)

(untitled) - Reiser, D.; Laubereau, A. (Chem. Phys. Lett., 1982)

(untitled) - Ghanadzadeh Gilani, A.; Moghadam, M.; Zakerhamidi, M. S. (Dyes Pigm., 2012)

(untitled) - Kawski, A.; Bojarski, P.; Kukliński, B. (Chem. Phys. Lett., 2008)

(untitled) - Kawski, A.; Bojarski, P. (Chem. Phys., 2010)

(untitled) - Kawski, A.; Kukliński, B.; Bojarski, P. (Chem. Phys., 2009)

(untitled) - Deye, J. F.; Berger, T. A.; Anderson, A. G. (Anal. Chem. (Washington, DC, U. S.), 1990)

(untitled) - Suppan, P. (Chem. Phys. Lett., 1983)

(untitled) - Suppan, P. (J. Photochem. Photobiol., A, 1990)

(untitled) - Dutta, A. K.; Kamada, K.; Ohta, K. (J. Photochem. Photobiol., A, 1996)

(untitled) - Sarkar, N.; Das, K.; Nath, D. N.; Bhattacharyya, K. (Langmuir, 1994)

(untitled) - Edward, J. T. (J. Chem. Educ., 1970)

(untitled) - Schuddeboom, W.; Jonker, S. A.; Warman, J. M.; Leinhos, U.; Kuehnle, W.; Zachariasse, K. A. (J. Phys. Chem., 1992)

(untitled) - Samsonova, L. G.; Selivanov, N. I.; Kopylova, T. N. (Opt. Spectrosc., 2014)

(untitled) - Zachariasse, K. A.; Demeter, A.; Druzhinin, S. I. (J. Phys. Chem. A, 2017)

(untitled) - Taniguchi, M.; Lindsey, J. S. (Photochem. Photobiol., 2018)

(untitled) - Chen, R.; Zhang, G.; Gao, Y.; Xiao, L.; Jia, S. (Appl. Phys. Lett., 2012)

Magnetic Properties - Van Krevelen, D. W.; Te Nijenhuis, K. (Elsevier, 2009)

(untitled) - Sultanova, N.; Kasarova, S.; Nikolov, I. (Acta Phys. Pol., A, 2009)

(untitled) - Tsuda, S.; Yamaguchi, S.; Kanamori, Y.; Yugami, H. (Opt. Express, 2018)

(untitled) - Clayton, L. M.; Sikder, A. K.; Kumar, A.; Cinke, M.; Meyyappan, M.; Gerasimov, T. G.; Harmon, J. P. (Adv. Funct. Mater., 2005)

(untitled) - Nasr, G. M.; Ahmed, R. M. (Mod. Phys. Lett. B, 2010)